Acute Kidney Injury Outcome in COVID-19 Patients (Iranian Journal of Kidney Diseases, 2022)
Introduction. Despite the high incidence of AKI in patients with COVID-19, the characteristics and consequences of this condition have not been well studied. Methods. This retrospective cohort study investigated the clinical characteristics, treatment methods, and outcome of COVID-19 patients aged 18 years and older who were hospitalized in Imam Hossein Hospital, Tehran, from February 20th, 2020 to June 20th, 2020. Results. Out of the total 367 patients with COVID-19, 104 (28%) patients were diagnosed with AKI at the time of admission or during hospitalization, 86 (23%) and 18 (5%) patients were diagnosed with the AKI on admission (early AKI) and after the first 24 h (late AKI), respectively. Concerning the AKI stages, 20 (19%) and 18 (17%) patients were in stages 2 and 3, and the cause of AKI in 52 (50%) patients was renal. Moreover, out of all patients with AKI, 25 (24%) and 29 (28%) patients had transient (Kidney function improvement within 48 h) and persistent AKI (kidney function improvement between 48 h to 7 days). Furthermore, 32 (31%) patients developed acute kidney damage (AKD) (no improvement in AKI after 7 days). The survival rate of AKI patients was lower in higher stages of AKI, and in cases that the reason for kidney dysfunction was renal or unknown. However, there was no difference in the mortality rate between the early and late AKI. Conclusion. Since about one-third of the patients with AKI eventually develop AKD, it is of great importance to closely monitor all COVID-19 patients, especially the high-risk ones, for the appropriate diagnosis and treatment of AKI.  DOI: 10.52547/ijkd.6610